The innovation drivers, strategies and performance of food processing SMEs in Malaysia - Abul Bashar Bhuiyan; Jamaliah Said; Md. Daud Ismail; Mohd Fauzi Mohd Jani; Yong, David Gun Fie (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Malaysian SMEs play an important role in sustaining the nation’s economic move toward a developed country status by 2020. The main aims of this study were to examine how the innovation drivers and the initiatives affect the performance of food procesing SMEs in Malaysia by analysing primary data gathered from 247 executives of food processing SMEs in Malaysia with statistical and econometric techniques. Multiple logistic regression models were employed to estimate how new innovations affect the annual sales turnover of SMEs in Malaysia. The study revealed that while the Malaysian SMEs were exploring innovations to maintain their performance and annual growth, multiple logistic regression model outputs showed that there were significant positive impacts of innovation, especially in the category of new product, new operational process, new managerial process, new markets and new sources of supply on the annual sales turnover of food processing SMEs in Malaysia. As such it is recommended that the Malaysian SMEs be considered as key drivers in improving the development of new products, new market and new sources of supply for sustainable performance and growth in the coming future.